Pengembangan Bahan Ajar Berbasis Digital Flipbook melalui Heyzine Flipbook untuk Kelas I SD - Ananta, Aura Zahra; Purwati, Panca Dewi (YASIN, 2025)
Although the use of digital media in teaching and learning has received considerable attention in previous studies, research that specifically examines the development of teaching materials based on Heyzine Flipbook to improve beginning writing skills and digital literacy among first-grade elementary school students remains limited. This study aimed to develop and evaluate the effectiveness of digital flipbook-based teaching materials as an interactive instructional medium for lower-grade students. A research and development (R&D) approach using the ADDIE model was employed, involving 17 first-grade students at SD Negeri Boyolali selected through purposive sampling based on learning needs. Data were collected using questionnaires, interviews, and observations, and were analyzed through thematic analysis and descriptive percentage techniques. The results show that the developed digital teaching materials obtained validity scores of 92–95% from material and media experts, which fall into the “very good” category, while student responses reached 99.46%, indicating that the medium is highly effective in increasing learning interest, material comprehension, and student engagement during beginning writing instruction. These findings contribute to the development of theory related to interactive digital learning media and broaden understanding of flipbook implementation in basic literacy instruction. The study concludes that visual–interactive, technology-based teaching materials are crucial in lower-grade learning and recommends that educators integrate flipbooks as supportive media for early literacy instruction, while also opening avenues for further research on the development of advanced features, expansion of sample coverage, and long-term evaluation of media effectiveness.